Pengaruh Pengalaman Kerja Terhadap Prestasi Kerja Dengan Kemampuan Kerja Sebagai Variabel Intervening - Mutholib Mutholib; Andre Risnadi (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
The purpose of this study was to analyze the direct or indirect effect of work experience, work ability on work performance. The sample in this study was as many as 52 who are employees of PT. Banua Sakti Mulia. This research was collected through a questionnaire which was processed and analyzed using Path Analysis. Then test the validity with and test the reliability. To test the hypothesis in this study using multiple linear regression analysis. The results of this study indicate that there is a positive and significant influence between work experience, work ability on work performance in employees, and there is an indirect effect of work experience on work performance through work ability, where employees who have a lot of work experience and have expertise in work then will also be able to improve employee performance, so that employees can excel in carrying out the work given.